Brain effects of computer-assisted cognitive remediation therapy in anorexia nervosa: A pilot fMRI study. (30th March 2016) - Brockmeyer, Timo; Walther, Stephan; Ingenerf, Katrin; Wild, Beate; Hartmann, Mechthild; Weisbrod, Matthias; Weber, Marc-André; Eckhardt-Henn, Annegret; Herzog, Wolfgang; Friederich, Hans-Christoph
Abstract: Poor cognitive-behavioral flexibility is considered a trait marker in anorexia nervosa (AN) that can be improved by cognitive remediation therapy (CRT). The present pilot study aimed at identifying changes in brain function potentially associated with CRT in AN. Data was obtained from a randomized, controlled trial. Twenty-four patients were assessed before and after 30 sessions of either CRT or a non-specific neurocognitive therapy. Voxel-wise analysis of whole brain functional magnetic resonance imaging was applied. Brain activation was measured during response inhibition and task switching. Although results did not reach significance, we found tentative support for CRT-related increases in brain activation in the dorsal putamen during task switching and in the dorsolateral prefrontal, sensorimotor and temporal cortex during response inhibition. These pilot findings provide viable pathways for future research on brain changes underlying CRT in AN. Highlights: Pilot fMRI study examined brain changes potentially related to CRT in AN. Data obtained from RCT comparing CRT and non-specific neurocognitive training. Tentative support for CRT-related increases in brain activation: . - increased brain activation in the dorsal putamen during task switching- increased brain activation in the DLPFC during response inhibition